Global trends and local realities: Lessons about economic benefits, selves and identity from a Swiss context - Csillagh, Virág (Studies in Second Language Learning and Teaching, 2015)
Inspired by the unexpected results of a standardized questionnaire survey of Swiss university students’ motivation and attitudes toward English, the paper discusses the influence of global and local contexts on language learners’ motivation and identity. As a result of the unprecedented spread of English as a foreign language (Crystal, 2003; Graddol, 2006), and, more importantly, the underlying social and economic issues that it reflects, elements of the global context intermingle with local realities to create new learning experiences, unaccounted for by traditional research paradigms. Individuals find themselves at the convergence of multiple contexts that affect and are in turn affected by their language attitudes and identity as well as sense of self. The intricate relationships between contexts and individuals continue to gain emphasis in current approaches to language learning motivation (cf. Dörnyei, MacIntyre, & Henry, 2015), which position L2 learnin in a new light, questioning the power and relevance of different motivational categories and also these of a generalizable theoretical model. The quantitative study presented in this paper explores interrelationships among key elements of the L2 motivational self system (Dörnyei, 2009) and a number of motivational factors on the one hand, contrasting them against the economic and social background of the Swiss context on the other. The findings of the project reveal that such repositioning of the participants in the multicultural, plurilingual environment of Geneva and its socioeconomic reality was indeed essential to the interpretation of the results since the extraordinary strength of external and societal factors in participants’ motivational profile gained meaning only in the light of the particularities of the local context. Therefore, the paper showcases the potential of a broader perspective on L2 motivation and the importance of learner-context relationships.